Empirical research on Innovation in Family Business: literature review and proposal of an integrative framework - Padilla-Meléndez, Antonio; Dieguez-Soto, Julio; Garrido-Moreno, Aurora (Review of Business Management, 2015)
Objective – The objective of this paper is to present the results of a systematic literature review on empirical research of innovation in Family Business (FB). Design/methodology/approach – A comprehensive literature review based on an in-depth analysis of 59 empirical studies was conducted. Findings – The revision presents an integrative framework, identifying the main determinants and dimensions of innovation; and summarizes the main research avenues and existing gaps, in order to guide future research. Practical implications – The paper summarises the main research advances in innovation in Family Business worldwide. Consequently, it allows to inform better decisions of managers of these firms. Originality – The study of innovation in Family Business has emerged as a prolific research area in recent years but the current state of knowledge of how these firms innovate is still fragmented and incomplete. Consequently, several calls have been made for further research in the area.